The Effect of Glycemic Control on Endothelial and Cardiac Dysfunction Induced by Red Blood Cells in Type 2 Diabetes - Mahdi, Ali; Jiao, Tong; Yang, Jiangning; Kövamees, Oskar; Alvarsson, Michael; von Heijne, Maaria; Zhou, Zhichao; Pernow, John (Frontiers in Pharmacology, 2019)
Red blood cells (RBCs) from patients with type 2 diabetes mellitus (T2DM) induce endothelial dysfunction and impair cardiac function following ischemia via increase in RBC arginase and oxidative stress. Here, we aimed to elucidate whether the effect of RBC-mediated cardiac impairment following ischemia and endothelial dysfunction in T2DM is dependent on glycemic control. Patients with T2DM at poor glycemic control (T2DM PGC), at improvement in glycemic control (T2DM IGC) and healthy subjects were recruited. Isolated RBCs from subjects were incubated with aortic rings from healthy Wild type rats with subsequent evaluation of endothelium-dependent relaxation (EDR) using wire myograph. Moreover, RBCs were perfused to isolated wild type rat hearts with subsequent evaluation of left ventricular developed pressure (LVDP) during reperfusion using Langendorff setup. In separate experiments, RBCs were pre-incubated with an arginase inhibitor before perfusion. Glucose and glycated hemoglobin were 38% and 31% respectively lower in T2DM IGC compared to T2DM PGC. RBCs from T2DM PGC and T2DM IGC impaired EDR to a similar magnitude compared to RBCs from healthy subjects. LVDP was significantly impaired in hearts given RBCs from T2DM PGC as compared to those from healthy subjects. The impairment of LVDP induced by T2DM PGC was fully attenuated by RBCs from T2DM IGC. Arginase inhibition improved LVDP to a similar extent between T2DM PGC and IGC groups. These observations indicate that glycemic control improves impairment in post-ischemic recovery but not endothelial function induced by RBCs from T2DM. Moreover, inhibition of RBC arginase improves cardiac function irrespective of glycemic control.